Robotics-Assisted Pediatric Oncology Surgery—A Preliminary Single-Center Report and a Systematic Review of Published Studies - Vatta, Fabrizio; Gazzaneo, Marta; Bertozzi, Mirko; Raffaele, Alessandro; Avolio, Luigi; Riccipetitoni, Giovanna (Frontiers in Pediatrics, 2022)
Aim The use of robotics-assisted surgery in oncology has been proved effective and safe in adults. Despite these results, the use of robotics has been rarely reported for pediatric oncology. Our review aims to evaluate the safety and feasibility of robotics-assisted surgery in this field, analyzing our experience and performing a systematic review of the most recent studies. Methods We reviewed all patients affected by an oncological disease who underwent a robotics-assisted procedure at our institute. We performed a systematic review of the literature from 2012 to 2021 on the subjects. Findings A total of 14 patients underwent robotics-assisted tumor resection. Eleven procedures (median age 13.2-years old) were carried out in children with adnexal lesions (seven tumor excision and four ovariectomies). Histological diagnosis was mature teratoma (six), serous papillary cystadenofibromas of the fallopian tube (two), ovarian serous cystadenoma (one), ovarian mucinous cystadenoma (one), and ovarian seromucinous cystadenoma. The median length of stay was 2 days. No recurrences or complications at a median follow-up of 2.1-years were observed. A 5-year-old girl underwent a complete posterior resection of a type 3 sacrococcygeal tumor with a robotics-assisted approach for the dissection of a possible intraabdominal residual component of the lesion. No intra- and postoperative complications were recorded. Complete excision of a recurrent differentiating neuroblastoma of the left para-renal region was performed on a 9-year-old girl. An idiopathic anaphylactic shock occurred 1 day after the procedure. At 9 months' follow-up, no local recurrences of the lesion were observed. Overall, we reported no conversion to open surgery. Lastly, a robotic excision of a growing left superior mediastinal intermixed ganglioneuroblastoma was performed on an 8-year-old girl with no postoperative complications. Follow-up was uneventful (7 months). In the literature, the rate of complications ranges from 0 to 28%, mainly related to difficult dissection and impaired anatomy. Conversion is reported in 5% of all oncological procedures, due to more invading tumors and altered anatomical features. No robotics-related complications were reported. Conclusion Robotics-assisted surgery in pediatric oncology has proven to be feasible. Nevertheless, its use should be limited to selected cases and performed by highly trained oncological surgeons. Preparation and patient positioning, alongside a correct port placement, are crucial to carrying out these procedures. Further innovations in robotics may allow a wider application of this technology in pediatric oncology.